2010
DOI: 10.1507/endocrj.k09e-215
|View full text |Cite
|
Sign up to set email alerts
|

GH-releasing Peptide-2 does not Stimulate Arginine Vasopressin Secretion in Healthy Men

Abstract: Abstract. Ghrelin has a stimulating effect on arginine vasopressin (AVp). however, it is not known whether GhRp-2, a synthetic ghrelin receptor agonist, also has a stimulating effect on AVp release in men. to determine whether the GhRp-2 test is useful for assessing AVp secretion, blood Acth, Gh, FSh, Lh, pRL, tSh and AVp levels, as well as glucose, osmolality, sodium and hematocrit, were measured before and 15, 30, 45 and 60 min after an intravenous bolus of 100 µg GhRp-2 in 10 healthy men with and without fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Previous studies in humans suggested that GHRP's ACTH-releasing activity may be mediated via CRH and/or AVP [3,5,7,11], or independent on both peptides [12]. Very recently, Kamoi et al [13] showed that GHRP-2 does not stimulate AVP secretion.…”
Section: Provocative Tests For Acth and Cortisol Secretionmentioning
confidence: 99%
“…Previous studies in humans suggested that GHRP's ACTH-releasing activity may be mediated via CRH and/or AVP [3,5,7,11], or independent on both peptides [12]. Very recently, Kamoi et al [13] showed that GHRP-2 does not stimulate AVP secretion.…”
Section: Provocative Tests For Acth and Cortisol Secretionmentioning
confidence: 99%
“…2) For assessment of pituitary function, in a random order with more than 8 h of overnight fasting with intervals of more than 1 week, a single dose (100 µg) of GHRP-2 [9,10], a single dose (0.1 U/kg) of regular insulin (Novo Nordisk, Tokyo, Japan) [3,4,5], a single dose of TRH (500 µg: hTRH "Tanabe" injection, Tokyo, Japan) and a single dose (10 mL) of HRHs combined with CRH (100 µg; hCRH "Mitsubishi" injection, Tokyo, Japan), GRH (100 µg; hGRH "Sumitomo" injection, Tokyo, Japan), LH-RH (100 µg: hLH-RH "Tanabe" injection, Tokyo, Japan ), and TRH [12], and a single dose (1 mg) of glucagon (Novo Nordisk, Tokyo, Japan) [14,15] were administered as an intravenous bolus and subcutaneous bolus injections, respectively, at 09:00. After one year later, these tests were repeatedly performed.…”
Section: Subjectmentioning
confidence: 99%
“…After one year later, these tests were repeatedly performed. As a first trial test, after more than 8 h of overnight non-fasting, a single dose (100 µg) of GHRP-2 was administered [10]. He remained supine for more than 30 min before the injections and throughout the study period.…”
Section: Subjectmentioning
confidence: 99%
See 2 more Smart Citations